Collect and record! : Jewish Holocaust documentation in early postwar Europe - Jockusch, Laura 1976- (The Oxford series on history and archives, 2012)
Early chroniclers of the Holocaust : Jewish historical commissions and documentation centers in the aftermath of the Second World War -- Khurbn-forshung : history writing as a Jewish response to catastrophe -- Writing French Judaism's "book of martyrdom" : Holocaust documentation in liberated France -- Writing Polish Jewry's "greatest national catastrophe" : Holocaust documentation in Communist Poland -- Writing history while sitting on packed suitcases : Holocaust documentation in the Jewish displaced persons camps of Germany, Austria, and Italy -- Joining forces to comprehend the Jewish catastrophe : the attempt to establish a European community of Holocaust researchers -- History writing as reconstruction : the beginnings of Holocaust research from the perspective of its victims -- Appendix : major participants in the Jewish historical commissions and documentation centers